Hatchability Performance Of Different Varieties Of Turkey - Pandian, C.; Sundaresan, A.; Omprakash , A.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was conducted for a period of 12 weeks to analyze the hatchability performance of different varieties of turkeys at the age of 30-42 weeks viz Native Turkey, Nandanam Turkey-I and Nandanam turkey-II . The mean per cent fertility of different varieties of turkeys were differed significantly (P<0.05). The native turkey recorded significantly low fertility when compared with others. Highly significant difference was observed between turkeys on mean per cent hatchability to total and fertile egg set. No significant difference was observed for mean per cent dead in germ and dead in shell in all varieties of turkeys.